Carnosol-mediated Sirtuin 1 activation inhibits Enhancer of Zeste Homolog 2 to attenuate liver fibrosis. (February 2018) - Zhao, Huanyu; Wang, Zhecheng; Tang, Fan; Zhao, Yan; Feng, Dongcheng; Li, Yang; Hu, Yan; Wang, Chao; Zhou, Junjun; Tian, Xiaofeng; Yao, Jihong
Graphical abstract: Abstract: Quiescent hepatic stellate cell (HSC) activation and subsequent conversion into myofibroblasts is the central event in hepatic fibrosis pathogenesis. Epithelial−mesenchymal transition (EMT), another vital participant in liver fibrosis, has the potential to initiate HSC activation, which promotes abundant myofibroblast production. Previous studies suggest that Enhancer of Zeste Homolog 2 (EZH2) plays a significant role in myofibroblast transdifferentiation; however, the underlying mechanisms remain largely unaddressed. Carnosol (CS), a compound extracted from rosemary, displays multiple pharmacological activities. This study aimed to investigate the signaling mechanisms underlying EZH2 inhibition and the anti-fibrotic effect of CS in liver fibrosis. We found that CS significantly inhibited CCl4 - and TGFβ1-induced liver fibrosis and reduced both HSC activation and EMT. EZH2 knockdown also prevented these processes induced by TGFβ1 in HSCs and AML-12 cells. Interestingly, the protective effect of CS was positively associated with Sirtuin 1 (SIRT1) activation and accompanied by EZH2 inhibition. SIRT1 knockdown attenuated the EZH2 inhibition induced by CS and increased EZH2 acetylation, which enhanced its stability. Conversely, upon TGFβ1 exposure, SIRT1 activation significantly reduced the level of EZH2 acetylation; however, EZH2 overexpression prevented the SIRT1 activation that primed myofibroblast inhibition, indicating that EZH2 is a target of SIRT1. Thus, SIRT1/EZH2 regulation could be used as a new therapeutic strategy for fibrogenesis. Together, this study provides evidence of activation of the SIRT1/EZH2 pathway by CS that inhibits myofibroblast generation, and thus, CS may represent an attractive candidate for anti-fibrotic clinical therapy.